Correlating Bulk Density (With Dockage) And Test Weight (Without Dockage) For Wheat Samples - Bhadra, Rumela; Casada, Mark E.; Boac, Josephine M.; Turner, Aaron P.; Thompson, Sidney A.; Montross, Michael D.; Maghirang, Ronaldo G.; McNeill, Samuel G. (My University, 2016)
In grain bins, the compaction of stored grain is caused by the overbearing pressure of the bulk material in the bin. To predict the amount of grain in the bin, compaction values must be determined based on the average bulk density (BD) of the stored material. However, BD is determined following the Federal Grain Inspection Service (FGIS) guidelines for measuring test weight (TW), which require that dockage be removed prior to measuring wheat TW. Thus, this creates a problem for predicting grain compaction and conducting inventory studies, because the average BD of the grain in a bin for these calculations should include dockage. Therefore, regression models between the TW without dockage and the BD with dockage were obtained based on the reported scale data during wheat harvest from three elevators located in Kansas and Oklahoma. A power model was used to predict BD with dockage when TW without dockage and dockage levels are given. Laboratory samples of HRW and SRW wheat with dockage levels ranging from 0.05% to 5% showed a second order polynomial trend when plotted against decrease in BD with dockage values compared to TW without dockage. These results will be crucial for determining grain packing inventory parameters for HRW wheat bins.
Citation: Bhadra, R., Casada, M. E., Boac, J. M., Turner, A. P., Thompson, S. A., Montross, M. D.,...McNeill, S. G. (2016) Correlating Bulk Density (With Dockage) And Test Weight (Without Dockage) For Wheat Samples. Applied Engineering in Agriculture. 32(6). 925-930. 10.13031/aea.32.11692
Keywords: Dockage; HRW; SRW; Stored Grain Inventory; Test Weight; Wheat